Synthesis and Absolute Configurations of Six Natural Phenylpropanoids. Issue 16 (10th April 2014) - Liu, Xue‐Lian; Chen, Hui‐Jun; Yang, Yang‐Yang; Wu, Yikang; You, Jun
Abstract: In an effort to find answers to the tantalizing questions about the absolute configurations of a group of long‐known natural phenylpropanoids with very similar structures but different signs for the optical rotations, the compounds in question were synthesized in enantiomerically pure form using Evans asymmetric alkylation to generate the stereogenic centres with predefined absolute configurations. The 1 H and 13 C NMR spectra of the synthetic products were very consistent with those reported for their natural counterparts. In most cases, the optical rotations were also consistent with the corresponding data for the natural samples. The new findings not only allowed unequivocal assignments of the absolute configurations for the natural products, but also revealed that the configurations of closely related compounds from the same plant may be different. Abstract : Optically active natural products isolated many years ago with undetermined absolute configurations and simple structures unavoidably raise tantalizing questions. Do the stereogenic centres have ( R ) or ( S ) configurations? Do compounds isolated at the same time from the same plant have the same absolute configuration? Using synthesis, the answers, though somewhat unexpected, can finally be known.